Metabolomic Analysis of Biosynthesis Mechanism of ε-Polylysine Produced by Streptomyces diastatochromogenes - Wang, Ziyuan; Guo, Fengzhu; Dong, Tianyu; Tan, Zhilei; Abdelraof, Mohamed; Wang, Zichen; Cui, Jiandong; Jia, Shiru (Frontiers in Bioengineering and Biotechnology, 2021)
ε-polylysine, a natural preservative with broad-spectrum antimicrobial activity, has been widely used as a green food additive and it’s now mainly produced by Streptomyces in industry. In previous work, a high-yield ε-polylysine strain 6#-7 was obtained from the original strain TUST. However, the biosynthesis mechanism of ε-polylysine in 6#-7 is still unclear. Herein, the metabolomic analyses of the biosynthesis mechanism of ε-polylysine in both strains are investigated. Results show that the difference on metabolisms between TUST and 6#-7 is significant. And based on the results of both metabolomics and enzymatic activity, a metabolic regulation mechanism of the high-yield strain is revealed. The transport and absorption capacity for glucose of 6#-7 is improved. And the activity of enzymes relating to ε-polylysine synthesis, such as Hexokinase, is strengthened. On the contrary, the activity of enzymes in the branched-chain pathways, such as Succinate dehydrogenase, is decreased. Meanwhile, the increase of trehalose, glutamic acid, etc. makes 6#-7 more resistant to ε-polylysine. Thus the ability of the mutagenized strain to synthesize ε-polylysine is enhanced and the strain 6#-7 can produce more ε-polylysine compared with the original strain. For the first time, the metabolomic analysis of biosynthesis mechanism of ε-polylysine in the high-yield strain 6#-7 is investigated and a possible mechanism is then revealed. These findings provide a theoretical basis for further improving the production of ε-polylysine.